Linking psycho-physical profiles to different training condition during COVID-19 confinement - Bonavolontà, V.; Cataldi, S.; Conenna, A.; Fischetti, F. (Journal of Human Sport & Exercise, 2021)
At the end of the period of home confinement due to Covid-19 lockdown, the 12-item Health Survey (SF-12) questionnaire was used to assess the quality of life. Participants also completed the Profile of Mood State (POMS) for the assessment of mood. Data were collected through an online form on a sample of 143 adults (71% aged 18-30, 12% 31-40, 11% 41-50 and 6% aged >50, 58% males and 42% females). Subjects were divided into 5 groups according to the corresponding training condition followed during the first lockdown. Training classes were carried out via online guided distance learning. 19 subjects (Group FT) received functional training classes as they did before the confinement. Group FTL (29 subjects) followed another functional training only during the lockdown. Group DT (46 subjects) continued a non-functional type training also during lockdown; group TL performed one training only during lockdown. Finally, group NT (25 subjects) received no training. Results from SF-12 showed no significant differences between groups. POMS result indicated that only the FT group had positive effects on anxiety and depression, whereas a functional training performed with a different program (FTL) resulted in no significant effects on anxiety compared to NA group.